Blunted increase in serum hepcidin as response to oral iron in HFE – hemochromatosis. (13th March 2011) - Sangwaiya, A; Manglam, V; Busbridge, M; Thursz, M; Arnold, J
Abstract : Introduction: Majority of patients with HFE hemochromatosis ( HFE -H) are homozygote for C282Y mutation. Studies suggest iron accumulation in most types of hemochromatosis is due to hepcidin deficiency. The precise link between hepcidin levels and iron absorption in HFE -H patients has been poorly understood. We measured hepcidin response to oral iron challenge (200 mg ferrous sulphate), in HFE -H (C282Y/C282Y) patients and compare to healthy controls (HC). Methods: Nine patients with C282Y/C282Y HFE -H along with 15 HC were recruited for the study. All HFE -H were iron depleted and studied at a time distant to phlebotomy. Hepcidin was measured using a published immunoassay method. Serum iron, ferritin and transferrin saturation (%TSAT) were measured using standard methods. The area under the curve (AUC) was calculated and compared between the two groups. Results: The basal serum hepcidin levels in patients with HFE -H were significantly low as compared to HC (p=0.0002) (table 1 ). Incremental serum hepcidin response seen in HC reached significance at 4 h post iron challenge (p=0.0085). There was no significant hepcidin response in HFE -H at 4 h (p=0.294) (figure 1 ). The overall hepcidin response was significantly lower in HFE -H as compared to HC (AUC: p=0.0127). Conclusion: Failure to mount a rapid hepcidin response to an oral iron challenge is one of the key mechanisms of iron accumulation in spite of prevailing excess body iron in HFE -H patients with C282Y/C282Y mutation.